2008
DOI: 10.1590/s1677-55382008000300002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radical prostatectomy techniques: open, laparoscopic and robotic assisted

Abstract: Introduction: To review the current status of laparoscopic radical prostatectomy (LRP) and robotic assisted radical prostatectomy (RALP) in relation to radical retropubic prostatectomy (RRP) in the management of localized prostate cancer. Materials and Methods: Between 1982 and 2007 published literature was reviewed using the National Library of Medicine database and the following key words: retropubic, laparoscopic, robotic, robot-assisted, and radical prostatectomy. Special emphasis was given to the technica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1
17

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 40 publications
5
37
1
17
Order By: Relevance
“…Therefore, we believe that this surgical technique is both feasible and reproducible, since residents could complete it even in their first procedures supervised by a professor with an average surgical time of 145.5 minutes. This result is comparable to other series reporting mean procedure times of 181 minutes for RRP, 219 minutes for LRP, and 179.5 minutes for RARP [16]. The ease of the procedure reported here is an advantage compared to video-assisted surgery, for which surgeons typically require more than 200 procedures to reach a plateau in the learning curve [16].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Therefore, we believe that this surgical technique is both feasible and reproducible, since residents could complete it even in their first procedures supervised by a professor with an average surgical time of 145.5 minutes. This result is comparable to other series reporting mean procedure times of 181 minutes for RRP, 219 minutes for LRP, and 179.5 minutes for RARP [16]. The ease of the procedure reported here is an advantage compared to video-assisted surgery, for which surgeons typically require more than 200 procedures to reach a plateau in the learning curve [16].…”
Section: Discussionsupporting
confidence: 84%
“…The operations were executed by second-year residents of our hospital's urology program, aided by one of the authors, who is a senior surgeon. All surgeries were performed as planned, without conversion to the Walsh technique, and had a similar duration to other RRP techniques [5,16]. Therefore, we believe that this surgical technique is both feasible and reproducible, since residents could complete it even in their first procedures supervised by a professor with an average surgical time of 145.5 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to blood loss, it appears that RALP is superior to open and laparoscopic RP (Frota et al, 2008). While early results are promising, some studies have reported higher complication rates with RALP compared with open RP: Hu et al (2008) showed an anastomotic stricture rate of 15.2% in the RALP group, compared with 12% in the open group.…”
Section: Results Of Different Types Of Rpmentioning
confidence: 99%
“…Because the urologists always seek less invasive and less morbid therapeutic options and the financial sources supplying health worldwide tend Clinical Urolo�y Clinical Urolo�y doi: 10.1590/S1677-55382010000600007 to support therapeutic modalities resulting in shorter hospitalization and early recovery, interest in radical perineal prostatectomy (RPP) has increased again in recent years (1,2). When compared to radical retropubic prostatectomy (RRP), laparoscopic or roboticassisted procedures have advantageous outcome data regarding duration of hospitalization, loss of blood, time needed to recover from the disease, and return to normal daily life (3). However, these advantages may also be offered by RPP, which additionally has some advantages such as lesser cost and shorter duration of operation (1,4).…”
Section: Introductionmentioning
confidence: 99%